1977
DOI: 10.1207/s15327752jpa4101_14
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Style Approach to Creative Thought

Abstract: Creative thinking was explored from several approaches to further understanding of the interrelationship of perception, personality, and cognition. College students (N = 45) were administered the Group Embedded Figures Test (GEFT), the Remote Associates Test (RAT), a questionnaire concerning RAT strategy, and two self-report scales. Field independent subjects were found to be significantly (p less than .001) more creative than field dependents. Correlations between the RAT and GEFT and the self-report measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…L. Miller, 2007;Noppe & Gallagher, 1977;Puccio, Wheeler, & Cassandro, 2004). However, cognitive styles have seldom been offered as an explanation to account for gender differences in creativity.…”
Section: Gender and Cognitive Strategymentioning
confidence: 99%
“…L. Miller, 2007;Noppe & Gallagher, 1977;Puccio, Wheeler, & Cassandro, 2004). However, cognitive styles have seldom been offered as an explanation to account for gender differences in creativity.…”
Section: Gender and Cognitive Strategymentioning
confidence: 99%
“…The author discovered a significant relationship between the LSI divergent/convergent styles and the combinations of intuition-perceiving and sensing-judging types. Jonassen (1980) found that field independence was the best predictor of students' performance on divergent tasks in an introductory instructional media course (see also Bloomberg, 1971;Noppe and Gallagher, 1977).…”
Section: Divergent-convergent Thinking and Its Measurementmentioning
confidence: 99%
“…Much of this work centered on the Mednicks' Remote Associates Test (Mednick & Mednick 1967). Rather than attempt a superfi cial review of the substantial work using this measure, we refer the reader to test reviews by Baird (1972), Bennett (1972), Vernon (1972a), and Backman & Tuckman (1978), to Worthen & Clark (1971) for a critique of the RAT and a possibly improved measure of remote associational ability, to Mendelsohn (1976) for a good review of his studies of attentional processes presumably underlying RAT performance, to Noppe & Gallagher (1977) for a cognitive-style ap proach to the RAT, and to Sobel (1978) for a very recent review of 18 studies examining the remote associates theory of creativity.…”
Section: Creativity and Other Sp Ecial Abilitiesmentioning
confidence: 99%